Intralymphatic immunization enhances DNA vaccination - Maloy, Kevin J. (The National Academy of Sciences, 2001)
Although DNA vaccines have been shown to elicit potent immune responses in animal models, initial clinical trials in humans have been disappointing, highlighting a need to optimize their immunogenicity. Naked DNA vaccines are usually administered either i.m. or intradermally. The current study shows that immunization with naked DNA by direct injection into a peripheral lymph node enhances immunogenicity by 100- to 1,000-fold, inducing strong and biologically relevant CD8(+) cytotoxic T lymphocyte responses. Because injection directly into a lymph node is a rapid and easy procedure in humans, these results have important clinical implications for DNA vaccination.